If it's not what You are looking for type in the equation solver your own equation and let us solve it.
m+2=3m
We simplify the equation to the form, which is simple to understand
m+2=3m
We move all terms containing m to the left and all other terms to the right.
+1m-3m=-2
We simplify left and right side of the equation.
-2m=-2
We divide both sides of the equation by -2 to get m.
m=1
| 3x-4=2x-5x+8 | | 3/5+5/3x=5/3+3/5x | | 49k^2z-42z^5=0 | | 5/2x+6=7/4x-8 | | -8=5y+27 | | 6x^2-5x-12=18 | | 4x/5=6/7 | | 7n+9=37 | | -5-y=-6 | | 6x^2-18x-108=0 | | 2m+3=3m-2 | | 4x^2+4x-168=0 | | 3x-(-2)=-1 | | x^2+10x=230 | | x^2+18x=300 | | (B+10)+15= | | 5x+2=17-3(x-7) | | 7x^3(3x^2-5x+7)= | | 3a+3a=16 | | 4x-8=37+9x | | 6+(x+4)= | | x^2+3x=238 | | 1.8+6n-3.2=76 | | 4*-24=20 | | 5-7x=-72 | | 1+-3(n+5)=-8 | | 19w=5w^2-4 | | 9x+(4+3x)= | | 5+x+3= | | (x^2+8)=(x^2+2x-2) | | (2+7)(2+5)=0 | | o/6 |